Determinan Status Gizi pada Anak Usia 5 - 6 Tahun - Dini Damayanti (MPI Press, 2022)
Introduction: Based on a preliminary study at TK Negeri Pembina 1, toddlers had a health status of 85.1, Good nutrition in 2015, and 83.6% of total malnutrition in 2017. 2015 6.38% and 2017 4.91%, 2015 overweight 6,38% and 2017 11.4%, overall overweight in 2015 2.12%, even 2017 0% Objectives: The purpose of this study is to clarify the relationship between parenting, physical activity, and consumption of junk food with the nutritional status of children aged 5-6 years Method: This type of research is quantitative with a cross-sectional design, namely research data collection techniques that are carried out at the same time (point time approach). This research was conducted in September 2021. The population in this study were mothers with children aged 5 - 6 years at TK Islam Cahaya, Perum Coco Garden, Klapanunggal, Klapanunggal District, Bogor Regency. The population of 48 children, The sampling technique used the Slovin formula, so and a sample of 32 respondents was obtained. Sampling in this study was carried out using the purposive sampling method. The dependent variable is the Nutritional Status of the Child, while the independent variable is the Parenting Pattern, Physical Activity, and Junk Food Consumption. The instrument used is a questionnaire while the analysis used is univariate and bivariate. Result: Most of the children aged 5-6 years were 21 respondents (65.6%), and most of the children's physical activity was moderate, namely 25 children (78.1%). Most of the children are classified as low in junk food consumption, namely 25 children (78.1%), and most of them have the same nutritional status as 25 children (78.1%). I was there. (0.606-19.396). Conclusions: There is a relationship between physical activity and nutritional status in children aged 5-6 years with a P-value of 0.000 OR = 9.333 (3,204-27,190). There is a relationship between the consumption of junk food and nutritional status in children aged 5- 6 years at TK Islam Cahaya Klapanunggal Bogor in 2022. P-value 0.001OR = 7,250 (2,919-18.009)